Cardiac arrest: resuscitation by manual massage - Ertuğrul, Ali (The Turkish Journal of Pediatrics, 1958)
A brief discussion of the possible causes of cardiac arrest, the importance of prompt recognition and treatment by cardiac massage, and a brief description of the technique of massage have been presented. A brief case history of an infant in which cardiac arrest occurred, followed by prompt cardiac massage, has been presented with a discussion of the role of cardiac massage as a life-prolonging factor.